Proprotein convertase subtilisin/kexin type 9 inhibitors protect against contrast-associated acute kidney injury in patients with atherosclerotic cardiovascular disease - Ma, Yu; Fan, Hui; Mi, Wei; Ma, Jing; Deng, Yong; Song, Yijie; Li, Ximing (Frontiers in Cardiovascular Medicine, 2024)
Background and Aims: Contrast-associated acute kidney injury (CA-AKI) may occur in patients undergoing medical procedures involving X-rays and radiocontrast media, potentially resulting in prolonged renal impairment. However, no effective treatments are available. Therefore, this study aimed to investigate the efficacy of evolocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor, in reducing CA-AKI incidence among patients with atherosclerotic cardiovascular disease (ASCVD) undergoing percutaneous coronary intervention. Methods: This retrospective cohort study included patients who underwent percutaneous coronary intervention between January 2020 and December 2021 at Tianjin Chest Hospital. The study endpoint was CA-AKI incidence, and the impact of selection bias and other potential confounding factors was mitigated using bias matching.Overall, 1,642 patients were included in this study: 821 patients received evolocumab treatment before contrast agent application, and 821 did not receive such treatment. Results: CA-AKI incidence was 6.21% and 8.04% in the evolocumab and control groups, respectively. After propensity-score matching, the incidence rate was 5.09% and 14.16% in the evolocumab and control groups, respectively. Evolocumab treatment significantly reduced CA-AKI incidence (p<0.001).Consistent findings were obtained in the subgroups of individuals with type II diabetes mellitus, chronic heart failure, and hypertension. Evolocumab exhibited a significantly greater protective effect in the high-and extremely high-risk populations than in the low-and middle-risk populations (p<0.001). Conclusions: Evolocumab administration significantly reduced CA-AKI incidence among patients with ASCVD. Notably, this effect was more prominent within the subset of high-and extremely high-risk individuals who were already experiencing CA-AKI.